2017
DOI: 10.1093/jee/tox233
|View full text |Cite
|
Sign up to set email alerts
|

Pupation Behavior and Predation on Drosophila suzukii (Diptera: Drosophilidae) Pupae in Maine Wild Blueberry Fields

Abstract: Drosophila suzukii (Matsumura; Diptera: Drosophilidae) is an invasive vinegar fly and pest of soft fruits in North America, including wild blueberries (Vaccinium angustifolium Aiton) in Maine. Despite its presence in the continental United States for 9 yr, little is known about its natural enemy complex. Here we report the results of a 3-yr study designed to identify naturally-occurring predators in Maine's wild blueberry fields. Experiments were conducted to determine pupation site and pupation depth to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 49 publications
2
41
0
Order By: Relevance
“…Although previous work using DNA extraction techniques revealed that F. auricularia are active in predation of SWD, it is likely that they consume more eggs, larvae and pupa than adults . Additionally, high levels of larval predation have been observed in other earwig species and a variety of different prey insects . Limited levels of SWD adult predation contrasted with significant corresponding reductions in SWD larval and emerged adult densities imply that adult predation accounted for little of the population suppression even though SWD were caged with the earwigs within this assay.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Although previous work using DNA extraction techniques revealed that F. auricularia are active in predation of SWD, it is likely that they consume more eggs, larvae and pupa than adults . Additionally, high levels of larval predation have been observed in other earwig species and a variety of different prey insects . Limited levels of SWD adult predation contrasted with significant corresponding reductions in SWD larval and emerged adult densities imply that adult predation accounted for little of the population suppression even though SWD were caged with the earwigs within this assay.…”
Section: Discussionmentioning
confidence: 82%
“…35 Additionally, high levels of larval predation have been observed in other earwig species and a variety of different prey insects. 28,29,40,41 Limited levels of SWD adult predation contrasted with significant corresponding reductions in SWD larval and emerged adult densities imply that adult predation accounted for little of the population suppression even though SWD were caged with the earwigs within this assay. Hence, F. auricularia may more easily predate immature stages of SWD, which are not capable of flight and so are easier to target.…”
Section: F Auricularia Biocontrol Of Swdmentioning
confidence: 92%
See 2 more Smart Citations
“…Drosophila suzukii 3rd instar larvae usually leave the fruit to pupate under the soil, 38,39 which as shown above, increases their chances of survival. Impeding larvae from reaching protection underground may be a valuable strategy to reduce D. suzukii population pressure.…”
Section: Discussionmentioning
confidence: 92%